Investigating the influence of germline ATM variants in chronic lymphocytic leukemia on cancer vulnerability - Roberta S. Azevedo; Francesca Morelli; Kiyomi Mashima; Rayan Fardoun; Svitlana Tyekucheva; Stacey Fernandes; Samantha Shupe; Marissa Terra; Anisha Patel; Matthew S. Davids; Joseph Yu; Jennifer R. Brown (Haematologica)
Chronic lymphocytic leukemia (CLL) patients have an increased risk of secondary cancers, along with predisposition to CLL in their relatives. We have previously identified germline ATM variants as associated with CLL risk; here, we present their impact on predisposition to secondary neoplasms in CLL patients and their relatives. Patients enrolled in our tissue bank who had germline ATM status available were mailed a questionnaire between April 2022 and May 2023. Of the 333 patients who replied to the questionnaire, 283 patients (85%) reported at least one relative with a cancer history. The prevalence of family history of B-cell lymphoproliferative disorders was significantly higher (p=0.02) in patients with germline ATM variants (32%) compared to those without germline ATM variants (21%) including familial CLL (25% vs 18%) (p=0.04). No significant difference in the prevalence of secondary cancers was found between patients with and without germline ATM variants (p=0.73), although the role for individual ATM variants in other malignancies could not be excluded given the small sample size. Time to first CLL treatment (TTFT) was shorter in patients harboring somatic ATM events while no difference was observed in patients with germline ATM variants. In conclusion, we demonstrate a higher prevalence of B-cell lymphoproliferative disorders, including familial CLL, in relatives of CLL patients carrying germline ATM variants. The presence of these germline variants did not impact TTFT compared to patients harboring somatic ATM mutations.